Implementation of Kaizen Culture in Administration to Improve Operations at PT. Surya Pratista Hutama (Suprama): Penerapan Budaya Kaizen dalam Administrasi untuk Meningkatkan Operasional Pada PT. Surya Pratista Hutama ( Suprama ) - Nisfullaili Hidayati (Procedia of Social Sciences and Humanities, 2026)
General Background: Efficient administrative operations are vital for sustaining business competitiveness in modern food industries. Specific Background: PT. Surya Pratista Hutama encounters operational hurdles due to inconsistent archiving practices and unstandardized document numbering in daily petty cash management. Knowledge Gap: Existing literature highlights administrative functions but lacks practical insights into continuous improvement frameworks within food manufacturing administration. Aims: This study evaluates administrative procedures and proposes a Kaizen-based continuous improvement framework to enhance operational efficiency. Results: Comparative qualitative analysis demonstrates that systematic archiving of delivery notes and sales invoices guarantees internal control, reliable audit trails, and precise financial reporting. Novelty: This research provides a novel practical integration of 5S principles into food industry administrative record-keeping. Implications: Implementing continuous improvement strengthens corporate compliance, streamlines audit procedures, and secures sustainable operational performance.  Keywords: Kaizen Culture, Administrative Management, Operational Efficiency, Document Archiving, Internal Control Key Findings Highlights Inconsistent document filing creates bottlenecks in internal audit processes and cash reconciliation. Archival of delivery orders and sales receipts serves as vital legal proof and accounting control. Stepwise adoption of Kaizen principles systematically optimizes daily corporate administration workflows.